2016
DOI: 10.1111/icad.12207
|View full text |Cite
|
Sign up to set email alerts
|

The role of high termitaria in the composition and structure of the termite assemblage in Miombo woodlands of southern Burundi

Abstract: Miombo woodlands cover extensive areas in southern and southeastern Africa, but are under high anthropogenic pressure. A conspicuous feature of this ecosystem is the presence of high termitaria (>2 m high) built by fungus‐growing termites (Macrotermitinae). Despite the fundamental role of termites in African ecosystems, miombo termite communities remain poorly known. We suspected high termitaria to play a structuring role for the whole termite assemblage of miombo woodlands in southern Burundi. In a formerly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…A second hypothesis is that the four spatial variables influencing the distribution of C. pallidiceps corresponds to spatial patterns related to dispersal capacities of C. pallidiceps or to the effects of biotic interactions (territoriality, competition or predation with other species) (Legendre, 1993;Pinto and MacDougall, 2010). Nduwarugira et al (2017) observed that at the local (quadrat of 5 m²) scale, the interactions between termite species were almost non-significant in the Rumonge Forest, which indicates that species do not defend permanent territories against each other. Nevertheless, colony mosaics, the behavioural mechanisms of territoriality and the ecological consequences of exclusive use of foraging space in termites may be analogous to those found in ants (Adams and Levings, 1987).…”
Section: Role Of Elevation and Soil Properties In The Distribution Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…A second hypothesis is that the four spatial variables influencing the distribution of C. pallidiceps corresponds to spatial patterns related to dispersal capacities of C. pallidiceps or to the effects of biotic interactions (territoriality, competition or predation with other species) (Legendre, 1993;Pinto and MacDougall, 2010). Nduwarugira et al (2017) observed that at the local (quadrat of 5 m²) scale, the interactions between termite species were almost non-significant in the Rumonge Forest, which indicates that species do not defend permanent territories against each other. Nevertheless, colony mosaics, the behavioural mechanisms of territoriality and the ecological consequences of exclusive use of foraging space in termites may be analogous to those found in ants (Adams and Levings, 1987).…”
Section: Role Of Elevation and Soil Properties In The Distribution Ofmentioning
confidence: 99%
“…Aggressive interactions have been described in the field in some termite species (Leponce et al, 1997;Traniello and Leuthold, 2000). Soil-feeding termites, mainly Apicotermitinae, were found to be highly diversified and abundant in the poor soil of Rumonge Forest (Nduwarugira et al, 2017) unlike C. pallidiceps, which seems to occur in limited areas of the ecosystem. Our results suggest that the distribution of Cubitermes genera in the area is mainly due to soil heterogeneity conditions and not to competition with Apicotermitinae.…”
Section: Role Of Elevation and Soil Properties In The Distribution Ofmentioning
confidence: 99%
“…Gisagara and Rumonge-Vyanda Reserve. These four places have been impacted by human activities for a long time, but preserved or regenerated forests are currently under protection by conservation organisations (Nduwarugira et al 2017).…”
Section: Collection Zones and Studied Speciesmentioning
confidence: 99%
“…Soldierless species are very abundant in Africa and the Neotropics, where they can locally make up more than 30% of the termite species diversity (Eggleton et al ., 1995, 2002; Bourguignon et al ., 2011, 2016b; Dahlsjö et al ., 2015, 2020; Nduwarugira et al ., 2017). This makes the Apicotermitinae one of the most diverse subfamilies of Termitidae.…”
Section: Introductionmentioning
confidence: 99%